2012
DOI: 10.1016/j.jalz.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

White matter imaging changes in subjective and mild cognitive impairment

Abstract: WM tract degeneration is prominent in SCI and MCI patients, and is at least in part independent of overlying gray matter atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
85
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 47 publications
18
85
1
Order By: Relevance
“…Interestingly, these microstructural changes were evident in the absence of obvious GM macrostructural changes. Our DTI findings in SMI are in line with previous studies that showed DTI changes as a sensitive marker of neurodegeneration in the early stage of AD prior to GM macrostructural changes [4,16,17]. We additionally highlighted variable degrees of WM microstructural changes in SMI subjects stratified to risk profiles, which could provide a better clinical relevance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, these microstructural changes were evident in the absence of obvious GM macrostructural changes. Our DTI findings in SMI are in line with previous studies that showed DTI changes as a sensitive marker of neurodegeneration in the early stage of AD prior to GM macrostructural changes [4,16,17]. We additionally highlighted variable degrees of WM microstructural changes in SMI subjects stratified to risk profiles, which could provide a better clinical relevance.…”
Section: Discussionsupporting
confidence: 90%
“…This can be explained by different characteristics of the two DTI parameters; decreased FA represents disrupted directionality of fibers, whereas increased MD represents increased water diffusivity [4]. Intriguingly, MD values correlate more with AD-associated GM changes than FA values, which was compatible with a previous report demonstrating MD as a better discriminating factor of early neurodegenerative changes in GM [4]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…human and animal models (Desai et al, 2009;Selnes et al, 2012). Perhaps most important, is the fact that at least some of the WM damage is related to the vascular changes, which are often represented as WM hyperintensities (Zhuang et al, 2010).…”
Section: Functional Organization and White Matter Integrity In MCImentioning
confidence: 99%
“…In these findings, the loss of WM volume or microstructural integrity, in key structures, appears to be measurable before gray matter differences. Similarly, in groups of subjects with and without subjective memory complaints, but scoring normally on all cognitive tests – thus encompassing very subtle differences – WM diffusivity of the posterior cingulate, retrosplenial cortex (RSC), and precuneus (Selnes et al, 2012) and parahippocampal WM (Wang et al, 2012) was significantly different for those with memory complaints, while gray matter thickness was not. Recent results such as these have been taken to suggest that early WM deterioration may be at least partially separate (Agosta et al, 2011; Selnes et al, 2012) from the β-amyloid and tau pathologies of gray matter, whose evolution is known to characterize Alzheimer’s disease (AD) (Braak and Braak, 1996), and have even raised the question whether Alzheimer’s should be considered a disease of the WM (Sachdev et al, 2013).…”
Section: Introductionmentioning
confidence: 98%